Si no sacas brillo a lo que te hace diferente, acabas siendo prescindible. - del Mar VAQUERO PÉREZ, María (Cirugía Plástica Ibero-Latinoamericana)
The article in the magazine "Ibero-Latin American Plastic Surgery" highlights the importance of emphasizing what makes us different in order to not be dispensable in the field of plastic surgery. The director of the magazine, María del Mar Vaquero Pérez, mentions the relevance of giving space to expression in Ibero-Latin American plastic surgery, promoting publication in Spanish and training in scientific writing. It emphasizes the pride of having been a means to encourage dissemination and sharing experiences in this field.